Dynamical indexation of risk in a virtual work environment. (30th April 2007) - Marsot, Jacques; Ciccotelli, Joseph; Marc, Jacques
When applying safety integration principles, work equipment designers are required to imagine future operating situations and assess a priori associated risk levels. Virtual reality techniques contribute partly to achieving this objective. Based on a feasibility study, this paper discusses the contribution of a dynamic risk-indexing tool applied in conjunction with these techniques. Following a brief reminder of the problem, this paper describes firstly the concepts underlying a generic model permitting a work situation risk index to be estimated. We then introduce the method retained for validating these virtual reality simulations. This focuses on the possibility of reproducing a reference activity through simulation. In spite of differences between the same task performed under real and virtual conditions, examples of industrial machinery is used to illustrate how risk indexing enables the designer to better assess the relevance of his choices and thus to act retrospectively on his design.